Recolonization of Bithynia Tentaculata (Linnaeus) (Mollusca, Gastropoda, Prosobranchia) in the Zone Affected by Heated Water Overflows From the Gentilly Nuclear Plant, Cuebec, Canada - Guy Vaillancourt; Richard Couture (Hello World!, 1977)
Following the shutdown of the reactor of the Gentilly (Quebec) nuclear generating plant, we have studied, during the years 1973 and 1974, the recolonization of Bithynia tentaculata in the hot water receptive zone. Our results were compared with those obtained in a zone farther upstream. It appears that the effects of thermal pollution are more than instantaneous and may still be present two years after the return to initial conditions.